Japanese Language Education and Examination for Indonesian Specified Skilled Worker (SSW) Candidates: An Analysis of the Pre-Departure Program - Ramdani, Andi Holik; Istiqamah, Waode Hanifah; Inoue, Tokiko (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2024)
This study examines how Japanese education prepares Indonesians for Japan’s specified skilled worker (SSW) programs. As economic ties between Indonesia and Japan grow, so does the demand for skilled labor in key sectors. Japan’s SSW program aims to attract foreign workers, including Indonesians, to fulfill these needs. Qualitative interviews were conducted with Indonesian sending organizations and candidates in preparatory programs for SSW visas. The research focuses on the Japanese language education framework, its alignment with industry requirements, curriculum development, teaching methodologies, and language proficiency training. The study also evaluates the impact of government policies and bilateral agreements on skilled migration between Indonesia and Japan. It aims to offer insights to policymakers, educators, and stakeholders to enhance educational programs and support mechanisms for better integration into the Japanese labor market. By visiting nearly 60 vocational training institutions licensed to send interns to Japan and several Sending Organizations (SO) with SP3MI permits, the study found that the SSW program has diversified teaching materials and introduced a new curriculum for Japanese language education in Indonesia. However, it has also led to a shortage of instructors in non- academic Japanese learning institutions. Additionally, uncertainty surrounding the language examination has caused many candidates to prefer the TITP over the SSW program. Addressing these issues from a human capital perspective, this study highlights the need for immediate measures such as sector-specific curricula and comprehensive instructor training to improve the quality of SSW candidates, thereby enhancing their experiences in Japan.